COMMUNICATION AND CLIMATE CHANGE: IMPACTS AND STRATEGIES FOR YOUTH ENGAGEMENT HOW CAN YOUTH LEAD THE FIGHT AGAINST CLIMATE CHANGE THROUGH INNOVATIVE COMMUNICATION? - Makabe, Morris; Siki Kigongo,; Jeremiah Rogito, (International Journal of Social Science, 2024)
Climate change is a key issue affecting diverse communities globally, demanding coordinated efforts across governmental and non-governmental spheres and all other actors. This paper explores the role of youth, in driving climate action through innovative communication strategies. Focusing on Africa, the paper examines how targeted communication can empower youth to become active climate advocates. Highlighting examples and best practices, this paper examines the importance of youth engagement in sustainable climate action and provides insights into effective communication approaches that align with Africa’s unique socio-cultural context The paper employed thematic analysis of relevant literature sourced from a wide range of databases to identify key trends and strategies. The findings presents the importance of context-specific approaches and presents the potential of youth-driven communication in advancing climate action. Suggestions for further research include exploring scalable models and the integration of digital tools to enhance youth engagement in climate action